Study on Damage Evolution Model of Sandstone under Triaxial Loading and Postpeak Unloading Considering Nonlinear Behaviors. (27th November 2021) - Zhou, Tianbai; Qin, Yueping; Cheng, Jian; Zhang, Xiaoyu; Ma, Qiufeng
Abstract : Conventional triaxial loading and unloading tests were carried out on sandstone samples in the Zigong area, of Sichuan Province, China. The changes in the elastic modulus of the unloading curves under different confining pressures were calculated, and the evolution law of the nonlinear properties of rock was analyzed. The results show that the rock is subjected to nonlinear damage during initial compaction, the elastic phase, destruction, and postpeak unloading. Moreover, the nonlinear behaviors of rock are restrained by the confining pressures. On this basis, a nonlinear stress-strain relationship affected by the average stress is proposed to describe nonlinear behaviors in the initial compaction stage. According to the test data, the evolution laws of various energies inside the rock during loading and unloading cycles are obtained. The results show that the external work is transformed into elastic energy and damage dissipated energy. Based on the energy analysis, the energy balance equation is established according to the law of energy conservation. By deriving the energy balance equation, the damage evolution equation of sandstone under triaxial loading is solved to establish a continuous constitutive model. The calculation results of the model are compared with the test results from two aspects of loading and postpeak unloading. The comparison results show that the proposed model, which reflects the whole stress-strain process and nonlinear properties of rock, could also describe the stress-strain relationship at the postpeak unloading stage to some extent.